The strategic planning process of GCIS (2012-2017) - Matlou, Karabo Hannah (My University, 2016)
The study examines the GCIS strategic planning process of 2012/13-2016/17 Strategic Plan that failed the requirements of the National Treasury Frameworks (NTF). This is in accordance with the 2012/13 AGSA report (Department of Government Communication and Information System, 2013). Although the strategic plan covers the period of five years, the financial years discussed are from 2012/13-2015/16 because the 2016/17 has not been implemented. A qualitative research approach was followed in identifying challenges in the GCIS strategic planning process; the purpose of the study is to offer recommendations to the GCIS management on improvement of the planning process. The South African public sector introduced an outcome-based planning approach in 2009, and developed the long-term plan which is the National Development Plan: Vision 2030 (NDP). In addition, NTF were drawn up and implemented to support the outcome-based approach. This approach to planning shifted the focus of government from outputs to outcomes and to the impact of service delivery on the lives of South Africans. The GCIS was mandated to ensure that there was a constant flow of information between the government and its citizens. The GCIS is responsible for providing strategic leadership in government communications within national, provincial and local government. In order to do this, it embarks on two planning processes, one to develop the National Communication Strategy and the other to develop the strategic plans of the GCIS. The NCS, in particular, guides communication within the government-wide communication system (GWCS). This study was conducted to answer the primary research question: (1) To what extent does the GCIS meet its strategic planning process? The literature review focuses on strategic planning processes in general and within the public sector in particular. The strategic planning process of the South African public sector gives context to the GCIS strategic planning process. A qualitative research design is followed, with in-depth interviews with the GCIS management, government communicators, members of the oversight bodies and a journalist. The findings from the research illustrate that the GCIS strategic planning process is not effective and does not meet the requirements of the NTF. It is not institutionalised as a management tool to improve the performance of the organisation. The challenges with the GCIS strategic planning process were identified as follows: (1) inadequate application of research to inform the strategic planning process, leading to poor formulation of strategies; (2) failure to set appropriate performance indicators and targets for the organisation as well as within the GWCS; (3) misalignment between the strategic plan and the National Communication Strategy (NCS), causing poor implementation of both documents; (4) prolonged acting leadership within the GCIS, which has caused instability in the organisation and unclear strategic direction; and (5) the need to identify planning approaches that are suited to addressing the dynamic and fluid communications environment. The study concludes with recommendations for the improvement of the GCIS strategic planning process to produce a credible strategic plan to meet the NTF requirements. The implementation of such a plan could enhance the efficient functioning of a GWCS.
Research is presented for the degree of Masters of Management in Public and Development Management to the Faculty of Commerce, Law and Management of the University of the Witwatersrand , March 2016
Keywords: Government Communication & Information System (South Africa); Government communication systems--South Africa; Information services--Government policy--South Africa; Strategic planning--South Africa